Analysis of Government Regulation Number 19 of 2005 Concerning PNBP At KUA, Ratu Agung Bengkulu - Muhammad Misbach; Ismail Jalili; Rohmadi; Suardi Abas (Journal of Sharia and Legal Science, 2023)
Marriage in Islam is a worship that is prescribed by Islam and is carried out perfectly according to the rules that have been set. The law that applies in Indonesia is the registration of marriages for Muslims by the Office of Religious Affairs (KUA). The aim of the research is to analyze the implementation of PP No. 19 of 2015 concerning PNBP in KUA, Ratu Agung District, Bengkulu City. This research is a type of qualitative descriptive research through library research. Data collection techniques with observation, interviews and documentation. The results of this study are that the implementation of PP PNBP at the KUA of Ratu Agung District is in accordance with the applicable provisions. In this case the community also welcomes the new regulations regarding marriage fees in accordance with Government Regulation No. 19 of 2015 concerning PNPB. There are several factors that influence people not to carry out marriages at the KUA because they are ashamed, they are considered not trying to find the cost of the marriage, they are unable to hold a party and they still believe that there will be a disaster if they get married at the KUA.